The Effect of Tiktok In Developing Student’s Speaking Skill at Grade 10 - Aldi Ardiansyah; Mukrim; Desrin Lebagi (LPPM Universitas Advent Indonesia, 2025)
This study examines the effectiveness of the TikTok application in developing the English- speaking skills of tenth-grade students at SMA Negeri 1 Dondo. The study employed a quasi-experimental pre-test–post-test design with two groups: an experimental group taught using TikTok and a control group taught using conventional methods. This research was conducted in response to students’ difficulties in speaking English, including limited vocabulary, inaccurate pronunciation, and low self-confidence. Pre-tests and post-tests were administered to measure students’ speaking performance before and after the treatment. The data were analyzed using SPSS to determine the effect of the intervention. The results showed a significant improvement in the experimental group’s speaking skills: the mean score increased from 68.10 (pre-test) to 79.00 (post-test), whereas the control group showed only a slight increase from 57.70 to 59.60. Statistical analysis confirmed that the use of TikTok significantly enhanced students’ speaking skills, particularly in terms of fluency and comprehension.